2016
DOI: 10.1186/s12903-016-0280-2
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of dental care among patients with severe mental illness: a study of a National Health Insurance database

Abstract: BackgroundThe oral health of patients with severe mental illness is poor, in general, and this may be attributed, in part, to inadequate dental care. This study investigated dental care utilization among patients with severe mental illness using a national representative sample.MethodsThis study used Taiwan’s National Health Insurance Research Dataset for 2009. Patients with the diagnosis of severe mental illness (ICD-9-CM: 290–298) were recruited as the study sample, and others comprised the control. Any visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 50 publications
1
39
0
Order By: Relevance
“…To cope with the universally poor oral health conditions among patients with SMI, multiple levels of strategies have been proposed, consisting of reorganization of dental services [26], increased accessibility to dental care [13], regular dental check-ups [19,27], undertaking aggressive preventive education programs [28], and improving oral health hygiene by means of educational intervention [29]. However, psychiatric patients are known to suffer from a variety of so-called negative symptoms, such as apathy and loss of drive, which would impede self-care and lead to neglect of oral hygiene [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To cope with the universally poor oral health conditions among patients with SMI, multiple levels of strategies have been proposed, consisting of reorganization of dental services [26], increased accessibility to dental care [13], regular dental check-ups [19,27], undertaking aggressive preventive education programs [28], and improving oral health hygiene by means of educational intervention [29]. However, psychiatric patients are known to suffer from a variety of so-called negative symptoms, such as apathy and loss of drive, which would impede self-care and lead to neglect of oral hygiene [13].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, oral health is often neglected by psychiatric personnel and the patients themselves [13]. Despite their worsening oral health, these patients receive less dental treatment than the general population [19,20]. To date, only a few studies have investigated the effects of oral health education or interventions on people with SMI.…”
Section: Introductionmentioning
confidence: 99%
“…Oral health tends to deteriorate as cognitive function declines (Martande et al, 2014;Ribeiro, Costa, Ambrosano, & Garcia, 2012). Reasons for this observation are likely multifaceted; for example, individuals with dementia often are limited by resources, capabilities for oral hygiene, and receive less dental care than the general population (Teng, Lin, & Yeh, 2016). Nevertheless, dementia has been found to be a strong predictor of poor oral health including the severity of periodontitis (Rapp, Sourdet, Vellas, & Lacoste-Ferre, 2017;Syrjala et al, 2012;Zenthofer et al, 2017;Zimmerman et al, 2017).…”
Section: Or Al He Alth and Cog Nitive Impairment-clinic Al S Tudie Smentioning
confidence: 99%
“…Furthermore, hospitals tend to provide substandard care for older adults with dementia . A study of the National Health Insurance database of Taiwan revealed that the rate of visit to a dental office was 27.2% in older adults with dementia, which is significantly lower as compared to the control population (48.3%) . Conversely, a recent systemic review suggested that an increased risk of cognitive impairment was observed amongst patients with suboptimal oral health .…”
Section: Introductionmentioning
confidence: 99%